2020
DOI: 10.1177/0040517520927009
|View full text |Cite
|
Sign up to set email alerts
|

The temperature effect on the inter-laminar shear properties and failure mechanism of 3D orthogonal woven composites

Abstract: Recent increases in the use of carbon fiber reinforced plastics, especially for high-temperature applications, has induced new challenges in evaluating their mechanical properties. The effects of temperature on the shear performance of 3-dimensional orthogonal and 2-dimensional plain woven composites were compared in this study through double-notch shear tests. A scanning electron microscope was employed to investigate the fiber/matrix interface properties to reveal the failure characteristics. The results sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…They reported that high temperatures could cause a progressive loss of matrix, thus the laminate degradation. Similarly, Li et al 22 characterized the interlaminar shear properties of three-dimensional orthogonal woven composites and showed that the ILSS decreased with increasing temperature ranging from 25 C to 150 C. This was associated with the degradation of the epoxy resin and the carbon/fiber/resin interface performance at high temperatures.…”
Section: Interlaminar Shear Strength (Ilss)mentioning
confidence: 93%
See 1 more Smart Citation
“…They reported that high temperatures could cause a progressive loss of matrix, thus the laminate degradation. Similarly, Li et al 22 characterized the interlaminar shear properties of three-dimensional orthogonal woven composites and showed that the ILSS decreased with increasing temperature ranging from 25 C to 150 C. This was associated with the degradation of the epoxy resin and the carbon/fiber/resin interface performance at high temperatures.…”
Section: Interlaminar Shear Strength (Ilss)mentioning
confidence: 93%
“…A minimal number of studies were carried out to study the performance of fiber-reinforced polymer composite laminates over time at high temperatures. [18][19][20][21][22] Li et al 18 investigated the mechanical properties of glass fiber reinforced polymer (GFRP) exposed to operating temperatures ranging from 100 to 350 C for a holding time of 0, 60, or 120 min. Ashrafi et al 19 studied the influence of elevated temperature and holding time (20 and 120 min) on the tensile properties of CFRP.…”
Section: Introductionmentioning
confidence: 99%
“…The results show that the thermal stress along the fiber direction is strong. Li et al 11 analyzed the effects of temperature on the shear performance of FRPC through double-notch shear tests, and the results showed that the shear strength decreased as temperature increased. Wen et al 12 established a meso-scale finite element model to analyze thermal residual stress of FRPC, the results show that the change in temperature and stress gradient led to cracking and peeling at the interface of fiber and matrix.…”
Section: Introductionmentioning
confidence: 99%
“…Fiber-reinforced composites (FRPs) composed of high-performance fibers and the resin matrix have been widely used in many fields such as aerospace and aviation, amongst other industries. The FRPs include various composites such as unidirectional composites (UDs), laminates, and woven, 1,2 braided 1,3 and stitched 4 composites. The UD is a composite with the simplest structure but is very important in the field of FRPs.…”
mentioning
confidence: 99%